Rhodium-Catalyzed Oxidative Cycloaddition of Benzamides and Alkynes via C–H/N–H Activation - Hyster, Todd K. (2010)
[Image: see text] The oxidative cycloaddition of benzamides and alkynes has been developed. The reaction utilizes Rh(III) catalysts in the presence of Cu(II) oxidants, and is proposed to proceed by N-H metalation of the amide followed by ortho C-H activation. The resultant rhodacycle undergoes alkyne insertion to form isoquinolones in good yield. The reaction is tolerant of extensive substitution on the amide, alkyne and arene, including halides, silyl ethers, and unprotected aldehydes as substituents. Unsymmetrical alkynes proceed with excellent regioselectivity, and heteroaryl carboxamides are tolerated leading to intriguing scaffolds for medicinal chemistry. A series of competition experiments shed further light on the mechanism of the transformation and reasons for selectivity.